2021
DOI: 10.3390/jcm10132973
|View full text |Cite
|
Sign up to set email alerts
|

Meteorin Is a Novel Therapeutic Target for Wet Age-Related Macular Degeneration

Abstract: The aim of this study was to evaluate the potential anti-angiogenic effect of MTRN (meteorin) in the laser-induced CNV rat model and explore its mechanisms of action. MTRN, thrompospondin-1, glial cell markers (GFAP, vimentin), and phalloidin were immuno-stained in non-human primate flat-mounted retinas and human retina cross sections. The effect of MTRN at different doses and time points was evaluated on laser-induced CNV at 14 days using in vivo fluorescein angiography and ex vivo quantification of CNV. A pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although the anti‐angiogenic effect was mediated by a decrease in vascular endothelial growth factor ( VEGF) in retinal neovascularization model (Wilkinson‐Berka et al, 2019), it was independent from VEGF and VEGF family members in choroidal neovascularization. This was related, at least in part, to the up‐regulation of decorin (Zhao et al, 2019) and meteorin (Delaunay et al, 2021), that exert anti‐angiogenic effects on choroidal neovascularization. It was also demonstrated that upon mineralocorticoid receptor activation by aldosterone, microglial cells exhibited not only a pro‐inflammatory but also a pro‐angiogenic phenotype (Rana et al, 2020; Wilkinson‐Berka et al, 2019) and that spironolactone reduced the number and the activation state of retinal microglia in rodent models of retinopathy of prematurity (Deliyanti et al, 2012; Wilkinson‐Berka et al, 2009), of choroidal neovascularization (Zhao et al, 2019) and of diabetic retinopathy (Zhao et al, 2021).…”
Section: Consequences Of Experimental Mineralocorticoid Receptor Path...mentioning
confidence: 99%
“…Although the anti‐angiogenic effect was mediated by a decrease in vascular endothelial growth factor ( VEGF) in retinal neovascularization model (Wilkinson‐Berka et al, 2019), it was independent from VEGF and VEGF family members in choroidal neovascularization. This was related, at least in part, to the up‐regulation of decorin (Zhao et al, 2019) and meteorin (Delaunay et al, 2021), that exert anti‐angiogenic effects on choroidal neovascularization. It was also demonstrated that upon mineralocorticoid receptor activation by aldosterone, microglial cells exhibited not only a pro‐inflammatory but also a pro‐angiogenic phenotype (Rana et al, 2020; Wilkinson‐Berka et al, 2019) and that spironolactone reduced the number and the activation state of retinal microglia in rodent models of retinopathy of prematurity (Deliyanti et al, 2012; Wilkinson‐Berka et al, 2009), of choroidal neovascularization (Zhao et al, 2019) and of diabetic retinopathy (Zhao et al, 2021).…”
Section: Consequences Of Experimental Mineralocorticoid Receptor Path...mentioning
confidence: 99%
“…However, the increased, although still rare, the occurrence of intraocular inflammatory adverse events (which can lead to vascular occlusion and vision loss) for this new molecule means a change in the treatment paradigm toward injections that are more spaced out is likely, helped by its improved efficacy [21]. In the coming years, the therapeutic arsenal will be totally transformed by numerous molecules in development [22], and the discovery of new therapeutic targets [23], with the aim of reducing the therapeutic burden and improving visual outcomes.…”
mentioning
confidence: 99%